Decrease of MYPT1 Is Critical for Impairment of NO-mediated Vasodilation in Mesenteric Artery of the Older Spontaneously Hypertensive Rats. Issue 3 (6th October 2021) - Cui, Yiqin; Yang, Liju; Liu, Xiaoqin; Che, Chang; Cheng, Jun; Li, Pengyun; Wen, Jing; Yang, Yan
Abstract: Nitric oxide (NO)-mediated vasodilatation is a fundamental response of vasculature, however, regulation of NO signaling pathway on resistance vessels in the older adult with hypertension is still unclear. The 16-week-spontaneously hypertensive rats (SHR), the 18-month-SHR (OldSHR), and the age-matched Wistar-Kyoto rats were used to study the changes of mesenteric resistance artery dilatation caused by sodium nitroprusside (SNP). After pre-vasoconstriction by norepinephrine (NE), the response of endothelium-denuded mesenteric artery ring to SNP was observed, and the changes in vascular response after pharmacological interventions of key nodes in the NO/sGC/cGMP/PKG1α signaling pathway were observed as well. RNA sequencing and functional enrichment analyses were used to provide information for conducting validation experiments. Vasodilation of NO in OldSHR was decreased, which significantly correlated with the reduction of PKG-mediated effect. Functional enrichment analysis of RNA sequencing showed that genes encoding important proteins such as sGC and MYPT1 (protein phosphatase 1 regulatory subunit 12A) were downregulated in OldSHR. Molecular biology validation results showed that mRNA expression of both α and β subunits of sGC were reduced, while mRNA and protein expression of PKG1α were reduced in OldSHR. More importantly, the expression of MYPT1 and p S668 -MYPT1 was significantly reduced in OldSHR, even under the treatment of SNP. The experiment also revealed an enhanced cAMP system in vasodilation in hypertension, while this function was completely lost in the OldSHR. Therefore, an NO-mediated decrease in vascular smooth muscle relaxation was found in the OldSHR. The dysfunction in cGMP-PKG signaling, in particular, decreased p S668 -MYPT1 was mechanistically involved.